A language of the interpersonal conflicts of the characters in the story “The Ukrainian diplomats” after G.F.Kvitka-Osnovjanenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with a language of the interpersonal conflicts of the characters in the story “The Ukrainian diplomats” after G.F.Kvitka-Osnovjanenko. The types of the characters focused on constructive and destructive decision of the conflicts are described. Conflictinal potential of the contents of the characters’ speech units is analysed, which results in misunderstanding between speakers, their emotional pressure, and negative result in coexistence.
Keywords: the interpersonal conflicts; the character; the speaker